2001
DOI: 10.1080/12265071.2001.9647616
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analyses of nuclear rDNAITSsequences of Koreanalliuml. subgenusRhizirideum(Alliaceae)

Abstract: Phylogenetic relationships among the Korean taxa of the genus Allium subgenus Rhizirideum and some related taxa were assessed on the basis of ITS sequences of nuclear ribosomal DNA. Twenty-eight accessions of the genus Allium L. consisting of subgenera Rhizirideum (19 taxa), Allium (5 taxa) and Amerallium (one taxon) were analyzed. The variation in the ITS region was informative at the levels of section except for sect. Reticulato-bulbosa which is known to be of multiple origin. The ITS 2 region was longer tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies of species in subgen. Rhizirideum have been conducted frequently in the past century (Shopova, 1966;Friesen, 1992;Dubouzet et al, 1997;Do and Seo, 2000;Raamsdonk et al, 2000;Kim et al, 2001;Lee, 2001;Raamsdonk et al, 2003;Ricroch et al, 2005;Friesen et al, 2006;Özler and Pehlivan, 2010;Rola, 2014;Li et al, 2016;Friesen et al, 2020). It was found that the chromosome base number of this subgenus was eight and the ploidy was mainly 2x or 4x.…”
Section: Introductionmentioning
confidence: 98%
“…Studies of species in subgen. Rhizirideum have been conducted frequently in the past century (Shopova, 1966;Friesen, 1992;Dubouzet et al, 1997;Do and Seo, 2000;Raamsdonk et al, 2000;Kim et al, 2001;Lee, 2001;Raamsdonk et al, 2003;Ricroch et al, 2005;Friesen et al, 2006;Özler and Pehlivan, 2010;Rola, 2014;Li et al, 2016;Friesen et al, 2020). It was found that the chromosome base number of this subgenus was eight and the ploidy was mainly 2x or 4x.…”
Section: Introductionmentioning
confidence: 98%